Fat-free mass index in a large sample of national collegiate athletic association men and women athletes from a variety of sports - Magee, M. K.; Fields, J. B.; Jagim, A. R.; Jones, M. T. (The Journal of Strength and Conditioning Research, 2024)
Fat-free mass index (FFMI) can be used to categorize fat-free mass (FFM) relative to height. Normative values have been established in a variety of sports, as has suggested lower and upper thresholds of FFMI. However, FFMI has not been reported in a large sample of athletes, representing both sexes and multiple sport types. The purpose of this study was to evaluate differences in FFMI and establish normative values across a large sample of collegiate sports. A total of 1,961 athletes (men: n = 596, 10 sports; women: n = 1,365, 8 sports) participated. Height and mass were measured using a stadiometer and calibrated digital scale, respectively. Fat-free mass was assessed with air displacement plethysmography and used to calculate FFMI. Kruskal-Wallis test and one-way analysis of variance evaluated differences in FFMI in women's and men's sports, respectively. When collapsed across sport type and stratified by sex, men had a higher FFMI (21.5 ± 1.9 kg·m-2 vs. 17.9 ± 1.8 kg·m-2; p < 0.001). Differences occurred in FFMI across sport. In women, basketball athletes had the highest FFMI (18.9 kg·m-2) and highest 99th percentile for FFMI, whereas rowers had the lowest (16.9 kg·m-2). In men, throwers had the highest FFMI (25.7 kg·m-2) and highest 99th percentile, whereas volleyball athletes had the lowest (19.9 kg·m-2). Differences in FFMI may be attributable to dietary habits and physiological demands of respective sports. These results can provide information relative to differences in FFMI values across sports. In addition, sport-specific normative values can be used as benchmarks and targets for training, nutrition, and goal setting.